2019
DOI: 10.1177/2164956119870984
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Yoga for Back Pain, Balance, and Maternal Wellness: A Randomized, Controlled Pilot Study

Abstract: Background The objective was to assess the feasibility of a prenatal yoga randomized controlled trial (RCT) for gestational low back pain (LBP), mobility, and maternal well-being. Methods In this pilot, women aged 18 to 39 years with uncomplicated pregnancies at 12 to 26 weeks were randomized, stratified by presence of LBP, to attend a weekly yoga class or a time-matched educational support group for 12 weeks. Sample size was based on anticipated enrollment of 2 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 54 publications
(54 reference statements)
2
51
0
8
Order By: Relevance
“…Three RCTs compared multiple interventions and only one of them was evaluated as of high methodological quality (Licciardone et al [ 24 ]) while the other two were evaluated as moderate (Keskin et al [ 23 ], Hensel et al [ 25 ]). Lastly, only one RCT for each of the following interventions was found: Kinesio tape (Kaplan et al [ 26 ]), yoga (Holden et al [ 27 ]), ear acupuncture (Vas et al [ 28 ]) and all of them were evaluated as moderate methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three RCTs compared multiple interventions and only one of them was evaluated as of high methodological quality (Licciardone et al [ 24 ]) while the other two were evaluated as moderate (Keskin et al [ 23 ], Hensel et al [ 25 ]). Lastly, only one RCT for each of the following interventions was found: Kinesio tape (Kaplan et al [ 26 ]), yoga (Holden et al [ 27 ]), ear acupuncture (Vas et al [ 28 ]) and all of them were evaluated as moderate methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…The research showed that the intervention was statistically important (p<0.001), but further study is required in order to determine that effect. Furthermore, Holden et al [ 27 ] in a moderate quality study examined yoga in comparison to educational attention and no difference was found.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study has been published that confirmed the positive effect of yoga during pregnancy on balance. Pregnant women that practised yoga had greater walking speed and were faster in the timed up-and-go test, had shorter double support and turn times during walking, which indicates they have better stability [50]. Pregnant women who exercised had beneficial adaptations to lower limb kinematics during gait [51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Hatha yoga did not have a signi cant effect on the pain score in both groups. The study of Holden et al (2019) also showed that yoga did not have a signi cant effect on the rate of low back pain by expressing the low back pain score on the visual analog scale (VAS) between the control and intervention groups in the second trimester of pregnancy. These results were consistent with the results of the current study (13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low back pain and sleep disorders during pregnancy have a major impact on pregnant women's ability to do their daily activities which worsens as pregnancy progresses (11). Unfortunately, despite the high prevalence of low back pain and sleep disorders during pregnancy (12) and their complications, there are limited or no treatments for them (13). In addition, these problems are often overlooked and not evaluated or treated by health care providers (12).…”
Section: Introductionmentioning
confidence: 99%